A comparative study to investigate the effect of orthodontic treatment on the uniqueness of the human anterior dentition. (August 2018) - Dyke, Alice Elizabeth Catherine; Cunningham, Susan; Hunt, Nigel; Ruff, Clifford
Highlights: Orthodontic treatment reduces the uniqueness of the human anterior dentition. Full Procrustes analysis created many false positive matches and is therefore unsuitable for this type of forensic work. Further research is necessary to investigate the uniqueness of the human anterior dentition within a larger population. Abstract: AIM: The human dentition contains many features which can be used to identify an individual from the dentition or from bite marks created and bite mark evidence may be used to link a suspect to a crime. The aim of this research was to investigate the effect of orthodontic treatment on the uniqueness of the human anterior dentition by comparison of the number of dental shape matches between pre- and post-treatment dental casts for a group of patients who have undergone orthodontic treatment (dental braces) to improve the alignment of their teeth. METHOD: This comparative study utilised pre- and post-orthodontic treatment dental casts from 36 patients. The dental casts were scanned and the anterior 6 teeth landmarked with 24 landmarks in total. The dental casts were divided into 4 groups: pre-orthodontic upper jaw (maxillary) and lower jaw (mandibular) and post-orthodontic maxillary and mandibular. Partial and full Procrustes analyses were undertaken to investigate the similarity between dental casts within each group and whether any of the comparisons were similar enough to be classified as a match. A landmarking repeatability study performed on a set of digitised dental casts determined the error of the landmarking procedure and allowed a proposed match threshold to be established. RESULTS: Orthodontic treatment reduced the uniqueness, and increased the similarity, between dentitions, as evidenced by a reduction in the maximum partial Procrustes distances in the post-orthodontic dental cast groups. None of the dental cast comparisons in the pre- or post-orthodontic maxillary or mandibular groups were classified as a match with the partial Procrustes analysis. However, many false positive matches (between 35 and 61) were identified within the post-orthodontic maxillary and mandibular groups using the full Procrustes analysis. CONCLUSIONS: Orthodontic treatment reduced the uniqueness of the human anterior dentition between different patients. There were no matches identified with the partial Procrustes analysis, but a large number of false positive matches were identified using the full Procrustes analysis. It is therefore proposed that full Procrustes analysis is unsuitable for this type of work and that only partial Procrustes analysis should be utilised.